Intelligent Greenhouse Monitoring System (IGMS) Integrated with GSM Technology - Saha, Arijit; Kritarth Kumar; Ria Jesmin; Satya; Vaibhav Gupta (Asian Journal of Electrical Sciences, 2019)
GSM technology can be used to monitor different parameters of environment like temperature, humidity, light intensity etc. Within greenhouse the soil and weather shall not depend on the natural agents. Greenhouses are controlled-area-environment to grow plants. Due to lack of availability of land for growing plants, greenhouses are the need of the day for growing crops and other plants. Intelligent greenhouse monitoring system (IGMS) is an advanced technological approach through which farmers of rural areas will be benefitted. Through this approach the direct human supervision is not required, which will save man power. In this communication an intelligent greenhouse monitoring system based on GSM technology is discussed within practical limits. In this current work, an automatic intelligent greenhouse monitoring system is built and tested in which the integrated GSM module sends information about temperature, humidity, light intensity, soil moisture and status of appliances (fan, artificial lights and water, pump etc.) that are connected for controlling the above mentioned greenhouse parameters. It has been found that the control obtained through this proposed system is excellent, and has the potential to be used commercially. To control the parameters according to preset values arduino has been programmed.